2019
DOI: 10.1002/adom.201901241
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Performance and Stability of Ternary Organic Solar Cells Utilizing Two Similar Structure Blend Fullerene‐Free Molecules as Electron Acceptor

Abstract: length region (the absorption peaks are located at 240 and 380 nm for [6,6]-phenyl-C61-butyric acid methyl ester (PCBM) and PC 71 BM, respectively) and the deep lowest unoccupied molecular orbital (LUMO) energy levels (the LUMO energy levels are 4.1 eV and 3.9 eV for PCBM and PC 71 BM, respectively). [6,7] Fullerene-free acceptors have recently been vigorously developed and replaced the common fullerene derivative small molecule acceptor materials for high-performance OSCs, which play an important role in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 72 publications
0
6
0
Order By: Relevance
“…The application of two NFAs in the ternary blend has also shown great potentials in improving the stability. [17,65,84,89,[213][214][215][216][217] Baran et al demonstrated the NFA-based binary and ternary blends could improve the storage lifetime and photostability in comparison to the low-bandgap polymer: fullerene solar cells. [65] In addition, they found that the introduction of O-IDTBR into PM6:Y6 binary blend could deactivate light-induced traps upon full sun illumination stress.…”
Section: Wwwadvmatde Wwwadvancedsciencenewscommentioning
confidence: 99%
“…The application of two NFAs in the ternary blend has also shown great potentials in improving the stability. [17,65,84,89,[213][214][215][216][217] Baran et al demonstrated the NFA-based binary and ternary blends could improve the storage lifetime and photostability in comparison to the low-bandgap polymer: fullerene solar cells. [65] In addition, they found that the introduction of O-IDTBR into PM6:Y6 binary blend could deactivate light-induced traps upon full sun illumination stress.…”
Section: Wwwadvmatde Wwwadvancedsciencenewscommentioning
confidence: 99%
“…In OSCs, determining the energy-level alignment of an acceptor is particularly important since the key photovoltaic parameter V OC is dependent on the difference (Δ E DA ) between the LUMO energy level of the acceptor and the HOMO energy level of the donor (Δ E DA = E LUMO (A)− E HOMO (D)) [ 30 , 31 ], which is essential to drive devices [ 32 ]. As shown in Figure 2 a, M B←N and M B-N possess relatively higher-lying HOMO levels than that of M C-N , indicating less energy loss ( E loss ) in the boron-containing acceptors.…”
Section: Resultsmentioning
confidence: 99%
“…The J SC and V OC values under different illumination intensities are calculated from Figure S4 and shown in Figure . The relationship between J SC and the light intensity ( P light ) can be described as , β is an exponential factor. The β values are 0.969 and 0.972 for the PBDB-T-2F:FOIC binary OPV and optimized ternary OPV, respectively.…”
Section: Resultsmentioning
confidence: 99%